Medium- and Large-Vessel Vasculitis. Issue 3 (19th January 2021) - Saadoun, David; Vautier, Mathieu; Cacoub, Patrice
Abstract : Systemic vasculitides are multisystem blood vessel disorders, which are defined by the size of the vessel predominantly affected, namely small, medium, or large vessels. The term "large vessel" relates to the aorta and its major branches; "medium vessel" refers to the main visceral arteries and veins and their initial branches. The most common causes of large-vessel vasculitis are giant cell arteritis and Takayasu arteritis, and those of medium-vessel arteritis are polyarteritis nodosa and Kawasaki disease. However, there is some overlap, and arteries of any size can potentially be involved in any of the 3 main categories of dominant vessel involvement. In addition to multisystem vasculitides, other forms of vasculitis have been defined, including single-organ vasculitis (eg, isolated aortitis). Prompt identification of vasculitides is important because they are associated with an increased risk of mortality. Left undiagnosed or mismanaged, these conditions may result in serious adverse outcomes that might otherwise have been avoided or minimized. The ethnic and regional differences in the incidence, prevalence, and clinical characteristics of patients with vasculitis should be recognized. Because the clinical presentation of vasculitis is highly variable, the cardiovascular clinician must have a high index of suspicion to establish a reliable and prompt diagnosis. This article reviews the pathophysiology, epidemiology, diagnostic strategies, and management of vasculitis.